2018
DOI: 10.1021/acs.chemrev.7b00629
|View full text |Cite
|
Sign up to set email alerts
|

Gas Permeation Properties, Physical Aging, and Its Mitigation in High Free Volume Glassy Polymers

Abstract: Hundreds of polymers have been evaluated as membrane materials for gas separations, but fewer than 10 have made it into current commercial applications, mainly due to the effects of physical aging and plasticization. Efforts to overcome these two problems are a significant focus in gas separation membrane research, in conjunction with improving membrane separation performance to surpass the Robeson upper bounds of selectivity versus permeability for commercially important gas pairs. While there has been extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
367
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 476 publications
(375 citation statements)
references
References 224 publications
(750 reference statements)
5
367
2
1
Order By: Relevance
“…Recent development of microporous polymers,s uch as polymers of intrinsic microporosity (PIMs), provides an ew platform for designing ion-exchange membranes with molecularly defined pore structures and size-exclusion function that enable fast and selective ion transport. [8] Previous work on ion transport PIMs has been focused on PIM-1 and application in organic solvent electrolytes. [9] In addition, we reported anew generation of anion-exchange membranes derived from Tr çger base-containing PIMs, [10] and demonstrated the fast transport of hydroxide and chloride anions through the subnanometer cavities within the positively charged polymer membranes.R ecent work also demonstrated that hydroxide exchange membranes and ionomers prepared from rigid backbones present improved ionic conductivity as well as high stability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent development of microporous polymers,s uch as polymers of intrinsic microporosity (PIMs), provides an ew platform for designing ion-exchange membranes with molecularly defined pore structures and size-exclusion function that enable fast and selective ion transport. [8] Previous work on ion transport PIMs has been focused on PIM-1 and application in organic solvent electrolytes. [9] In addition, we reported anew generation of anion-exchange membranes derived from Tr çger base-containing PIMs, [10] and demonstrated the fast transport of hydroxide and chloride anions through the subnanometer cavities within the positively charged polymer membranes.R ecent work also demonstrated that hydroxide exchange membranes and ionomers prepared from rigid backbones present improved ionic conductivity as well as high stability.…”
Section: Introductionmentioning
confidence: 99%
“…and polymers, have attracted extensive attention . Despite the fact that great achievements have been made, these membranes still suffer from phase segregation and low durability stemming from sliding of the linear polymer chains …”
Section: Methodsmentioning
confidence: 99%
“…For a long time, polydimethylsiloxane was one of the most gas permeable polymer . Later, glassy nanoporous Si‐substituted polymers like polynorbornenes , PIMs , and polyalkynes were synthesized that were found to be much more permeable than polysiloxanes. Furthermore, these new polymers unexpectedly displayed a salient feature for glassy polymers—the solubility‐controlled permeation of hydrocarbons .…”
Section: Introductionmentioning
confidence: 99%